2002
DOI: 10.3406/rfeco.2002.1517
|View full text |Cite
|
Sign up to set email alerts
|

Croissance économique et diffusion des TIC : le cas de la France sur longue période (1980-2000)

Abstract: [fre] Croissance économique et diffusion des TIC : le cas de la France sur longue période (1980-2000) La contribution des technologies de l'information et de la communication (TIC) à la croissance du PIB et de la productivité du travail serait en France de l'ordre de 0,2 à 0,3 % par an sur l'ensemble de la période 1980- 2000. Elle aurait connu une forte augmentation sur la seconde moitié des années 1990, en même temps que la contribution de la productivité globale des facteurs. Cette contribution des TIC serai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(15 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…However, since national accountants have been following the recommendations of the OECD-Eurostat Software Task Force, the measure of investment in software is more homogenous across countries. For example, the share of software in total ICT investment is comparable in the four countries (between 50% and 60%), while the previous data indicated that this share was twice as high in the United States as in France (see Cette, Mairesse and Kocoglu, 2000 [50] and 2002a [33]). Although this international harmonisation has made international comparisons of ICT contributions to productivity growth more robust, progress still needs to be made with regard to the measurement of own account software and the quality effect.…”
Section: C) the Contribution Of Icts To Productivity Growthmentioning
confidence: 84%
See 3 more Smart Citations
“…However, since national accountants have been following the recommendations of the OECD-Eurostat Software Task Force, the measure of investment in software is more homogenous across countries. For example, the share of software in total ICT investment is comparable in the four countries (between 50% and 60%), while the previous data indicated that this share was twice as high in the United States as in France (see Cette, Mairesse and Kocoglu, 2000 [50] and 2002a [33]). Although this international harmonisation has made international comparisons of ICT contributions to productivity growth more robust, progress still needs to be made with regard to the measurement of own account software and the quality effect.…”
Section: C) the Contribution Of Icts To Productivity Growthmentioning
confidence: 84%
“…As stressed in Cette, Mairesse and Kocoglu (2000) [37], (2002) [33,34], the relative importance attached to these two effects in growth accounting analyses depends to a great extent on the methodological choices and practises of statisticians and national accountants in measuring prices and dividing the ICT investment series in terms of nominal values in the corresponding series in terms of "volumes" (say at the prices of the preceding year) and of price changes. Schematically, the more the estimation of price changes takes into account the improvements in ICT performances (through substantially upgraded products or new products), by relying in particular on hedonic methods, the larger is the contribution of capital deepening to productivity gains and the lower that of TFP, and conversely.…”
Section: The Contribution Of Icts To Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Un tel constat est rappelé dans de nombreuses analyses, par exemple Gordon (2000) 4 , Stiroh (2001) ou Cette, Mairesse et Kocoglu (2000, 2002a. Il amène à relativiser la signification économique d'éventuelles inflexions du rythme estimé de la productivité multifactorielle.…”
Section: Les Effets Sur La Croissance Potentielle De Moyen à Long Termeunclassified